INNOVATION IN ARABIC SPEAKING LEARNING DURING PANDEMIC: A STUDY AT MAN PEMATANGSIANTAR / INOVASI PEMBELAJARAN MAHARAH KALAM PADA MASA PANDEMI (STUDI DI MAN PEMATANGSIANTAR) - Yogi Muhammad Akbar; Nuril Mufidah (Lughawiyah: Journal of Arabic Education and Linguistics, 2022)
This study aims to describe an innovation in Arabic learning especially in Arabic speaking skill by teachers at MAN Pematangsiantar during pandemic era in 2020-2022. This research used descriptive qualitative method. Source of data were Arabic teacher and students grade XI and XII. Data were collected by doing interview and observation, and then analyzed using interactive analysis model. Results showed that during pandemic in 2020-2022, teacher made an innovation in teaching Arabic speaking skill by applying various online media such as e-learning, Whatsapp group, Zoom Cloud Meeting, Google Meet, Google Classroom, and also making instructional video. The media were helpful in teaching Arabic speaking skill during pandemic because each of them has specific features that can be used to send materials, meet the students virtually, practice speaking, and also evaluate studentsâ€™ ability. However, teacher also faced some problems namely not proficient in operating the media, cannot control the students maximally, and unstable network.Â